Carencia de los valores morales y su incidencia en el comportamiento de los estudiantes del tercer año de educación básica de la Escuela Dr. Víctor Manuel Andrade Lara - Parra Logroño, Mariuxi Beatriz (2020)
In the School of Basic Education “Dr. Víctor Manuel Andrade Lara ”of the Pimocha Canton Babahoyo Parish Los Ríos Parish, students, a very high percentage come from environments where affection is lacking, others have suffered separation from the family nucleus and this has caused in them an unstable emotional development, others Students belong to homes that lack values, poor technology management results in inappropriate behavior and unsatisfactory school performance. Which demonstrates that the family plays a very fundamental role in the formation of a person with moral values, although these must be instilled during the education that is received in the classrooms but it is not necessary to isolate the parent since they are the main responsible for promoting in their children, especially by example, the moral values they deem necessary and desirable. For this reason I have enhanced this research, to design a didactic manual of moral values, for teachers and thus strengthen an education in moral values that helps the student to improve their school behavior.